Website Based School Information System at SMP Negeri 4 Kemangkon using Rapid Application Development Method - Pangestu, Hari; Abdul Azis; Agung Prasetyo (JINAV: Journal of Information and Visualization, 2024)
This research presents a website-based School Information System at SMP Negeri 4 Kemangkon using the Rapid Application Development (RAD) method. Education, the central pillar of human resource development, requires innovation, especially in applying computerized and internet-connected information systems. Website-based information systems are a solution to facilitate users' access to information, including at SMP Negeri 4 Kemangkon. The formulation of the problem in this study is how to build a website-based school information system at SMP Negeri 4 Kemangkon using the RAD method to facilitate the dissemination of school information and become an effective promotional media. Black Box testing on the functional aspects of this system resulted in 100% validity, signifying the success of system features in meeting requirements and operating without technical problems. The research results in the form of a School Information System of SMP Negeri 4 Kemangkon that can be implemented as an information service and promotional media. This website presents various services, including new student registration (PPDB), extracurricular activities, school vision & mission, teacher data, school contacts, school news, and other information. Overall, this research illustrates the successful development of a school information system with the RAD approach, making a positive contribution in facilitating the dissemination of information and being effective as a school promotion media. Suggestions for future research can be focused on evaluating the system's effectiveness after implementation and developing additional features to improve user experience.